Analysis of fabric evolution and metamorphic reaction progress at Lago della Vecchia-Valle d’Irogna, Sesia-Lanzo Zone, Western Alps - Luca Corti; Gioele Alberelli; Davide Zanoni; Michele Zucali (Journal of Maps, 2017)
The Lago della Vecchia-Valle d’Irogna rocks are part of the Eclogitic Micaschists Complex (EMC) of the Sesia-Lanzo Zone, western Austroalpine domain. The 1:10,000 scale map includes metaintrusive, minor micaschist, banded gneiss, and metabasic boudins. The multiscale structural analysis reveals successive magmatic and tectono-metamorphic stages: during M0 the metaintrusive protoliths emplaced; D1 took place under eclogite-facies conditions; during D2 stage, a pervasive foliation developed under retrograde blueschist-facies conditions; D3–D4 and D5 structures developed under greenschist-facies conditions; during M6 andesitic dykes intruded. The mapped degree of fabric evolution (FE) and metamorphic transformation (MT) related to D2-foliation shows that the MT was not only controlled by bulk rock and mineral compositions, but also by FE. The development of a pervasive blueschist-facies D2-foliation is in contrast with the eclogitic dominant fabric generally recorded in the EMC. This difference suggests that FE and MT are potentially responsible for km-scale heterogeneities in the tectono-metamorphic record.